Effects of elexacaftor/tezacaftor/Ivacaftor therapy on lung clearance index and magnetic resonance imaging in patients with cystic fibrosis and one or two F508del alleles - Gräber, Simon Y.; Renz, Diane M.; Stahl, Mirjam; Pallenberg, Sophia T.; Sommerburg, Olaf; Naehrlich, Lutz; Berges, Julian; Dohna, Martha; Ringshausen, Felix C.; Doellinger, Felix; Vitzthum, Constanze; Röhmel, Jobst Fridolin; et al. (American journal of respiratory and critical care medicine, 2022)
Rationale: We recently demonstrated that triple-combination CFTR (cystic fibrosis transmembrane conductance regulator) modulator therapy with elexacaftor/tezacaftor/ivacaftor (ELX/TEZ/IVA) improves CFTR function in airway and intestinal epithelia to 40-50% of normal in patients with cystic fibrosis (CF) with one or two F508del alleles. In previous studies, this improvement of CFTR function was shown to improve clinical outcomes; however, effects on the lung clearance index (LCI) determined by multiple-breath washout and abnormalities in lung morphology and perfusion detected by magnetic resonance imaging (MRI) have not been studied. - Objectives: To examine the effect of ELX/TEZ/IVA on LCI and lung MRI scores in patients with CF and one or two F508del alleles aged ⩾12 years. - Methods: This prospective, observational, multicenter, postapproval study assessed LCI and lung MRI scores before and 8-16 weeks after initiation of ELX/TEZ/IVA. - Measurements and Main Results: A total of 91 patients with CF, including 45 heterozygous for F508del and a minimal function mutation (MF) and 46 homozygous for F508del, were enrolled in this study. Treatment with ELX/TEZ/IVA improved LCI in F508del/MF (−2.4; interquartile range [IQR], −3.7 to −1.1; P < 0.001) and F508del homozygous (−1.4; IQR, −2.4 to −0.4; P < 0.001) patients. Furthermore, ELX/TEZ/IVA improved the MRI global score in F508del/MF (−6.0; IQR, −11.0 to −1.3; P < 0.001) and F508del homozygous (−6.5; IQR, −11.0 to −1.3; P < 0.001) patients. - Conclusions: Our data demonstrate that improvement of CFTR function by ELX/TEZ/IVA improves lung ventilation and abnormalities in lung morphology, including airway mucus plugging and wall thickening, in adolescent and adult patients with CF and one or two F508del alleles in a real-world, postapproval setting. - Clinical trial registered with www.clinicaltrials.gov (NCT04732910).
Gesehen am 13.03.2023